Minimal Invasive Circumferential Management of Thoracolumbar Spine Fractures. (16th November 2015) - Pesenti, S.; Graillon, T.; Mansouri, N.; Rakotozanani, P.; Blondel, B.; Fuentes, S.
Abstract : Introduction . While thoracolumbar fractures are common lesions, no strong consensus is available at the moment. Objectives . The aim of this study was to evaluate the results of a minimal invasive strategy using percutaneous instrumentation and anterior approach in the management of thoracolumbar unstable fractures. Methods . 39 patients were included in this retrospective study. Radiologic evaluation was based on vertebral and regional kyphosis, vertebral body height restoration, and fusion rate. Clinical evaluation was based on Visual Analogic Score (VAS). All evaluations were done preoperatively and at 1-year follow-up. Results . Both vertebral and regional kyphoses were significantly improved on postoperative evaluation (13° and 7° versus −1° and −9° P < 0.05, resp.) as well as vertebral body height (0.92 versus 1.16, P < 0.05 ). At 1-year follow-up, mean loss of correction was 1°. A solid fusion was visible in all the cases, and mean VAS was significantly reduced form 8/10 preoperatively to 1/10 at the last follow-up. Conclusion . Management of thoracolumbar fractures using percutaneous osteosynthesis and minimal invasive anterior approach (telescopic vertebral body prosthesis) is a valuable strategy. Results of this strategy offer satisfactory and stable results in time.